If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 = v + 2 Reorder the terms: 12 = 2 + v Solving 12 = 2 + v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-1v' to each side of the equation. 12 + -1v = 2 + v + -1v Combine like terms: v + -1v = 0 12 + -1v = 2 + 0 12 + -1v = 2 Add '-12' to each side of the equation. 12 + -12 + -1v = 2 + -12 Combine like terms: 12 + -12 = 0 0 + -1v = 2 + -12 -1v = 2 + -12 Combine like terms: 2 + -12 = -10 -1v = -10 Divide each side by '-1'. v = 10 Simplifying v = 10
| (4+4i)+(-5+7i)-8i= | | 8(-3b+6)=96 | | 1.3n-.03=9 | | 4xy^2/y | | 20×1/4 | | x^2-40=41 | | 3(2l+10)=48 | | y+x=10-4 | | 3x+22=x+4 | | 0.6(x-1)+0.2x=6.6 | | y=-2.1x+3.4 | | -x-19=2x+8 | | 49=-7z | | y=2x^2-36x+c | | -2(x+2)+3=3(x+3)+4 | | (x-2)(x-2)+(y-6)(y-6)=25 | | 2+f=-3 | | x-6+x=78 | | -y/4=-16 | | 2x=960 | | x^3+4=13 | | -6(2t+8)=-108 | | 43+x=-37 | | x^4+5x^3-x^2-12x-6=0 | | 7x+21=3x+1 | | -6(27+8)=-108 | | b-38=-28 | | -3x^2+9x=2 | | 3(1.5+5y)=30 | | -6(27+8)=-180 | | 3(1+5y)=30 | | -11z=99 |